BIRC5 (Survivin) Splice Variant Expression Correlates With Refractory Disease and Poor Outcome in Pediatric Acute Myeloid Leukemia: A Report From the Children's Oncology Group - Moore, Andrew S. (Pediatr Blood Cancer, 2013)
BACKGROUND: The inhibitor-of-apoptosis protein survivin, encoded by BIRC5, regulates apoptosis, cell division and proliferation. Several survivin splice variants have been described however, the prognostic significance of their expression has not been well defined in pediatric acute myeloid leukemia (AML). PROCEDURE: Quantitative expression analyses of BIRC5 mRNA (n = 306) and survivin transcript splice variants (n = 90) were performed on diagnostic bone marrow samples from children with de novo AML treated on the clinical trials CCG-2961 and AAML03P1, then correlated with disease characteristics and clinical outcome. RESULTS: Total BIRC5 expression did not correlate with clinical outcome. Fragment length analysis and sequencing of the entire BIRC5 transcript demonstrated three splice variants. The most prominent product, wild-type survivin, was expressed in all samples tested. Two minor transcripts were present in 90 patients treated on CCG-2961; survivin-2B and a novel variant, survivin-ΔEx2, characterized by deletion of BIRC5 exon II. A high 2B/ΔEx2 expression ratio (≥1) correlated with increased diagnostic WBC count, monocytic phenotype, +8 cytogenetics, lower complete remission (45% [n = 10] vs. 88% [n = 59], P < 0.001) and higher induction failure rates (23% [n = 5] vs. 3% [n = 2], P = 0.009). Consistent with this poor induction response, patients with a 2B/ΔEx2 ratio ≥1 had inferior 5-year survival rates (OS 36% vs. 60%, P = 0.011; EFS 23% vs. 53% at 5 years, P = 0.001) and appear to have increased relapse risk (P = 0.056). Subset analyses suggest that relative over-expression of 2B, rather than under-expression of ΔEx2 determines clinical response. CONCLUSIONS: High survivin-2B/ΔEx2 ratios are associated with refractory disease and inferior survival in childhood AML. Survivin splice variant expression warrants prospective evaluation in clinical trials.